One thousand makers of the millennium. - 1000 makers of the millennium (London D. Kindersley, 1999)
Biographies of 1000 leaders, thinkers, scientists, inventors, artists, and writers who had an impact on our world. Includes a timeline
One thousand makers of the millennium
Keywords: Biography -- Juvenile literature; Chronology, Historical -- Juvenile literature; Biography; World history